Testing Process of Density and Porosity of Aluminium 7075 and Aluminium 6061 - Ariyanto, Ariyanto; Ahmad Risa Harfit; Ahcmad Fauzan; Tati Noviati; Bagus Rianto (Asosiasi Dosen Muda Indonesia, 2025)
Abstract: Aluminium is a lightweight metal with good corrosion resistance and electrical conductivity properties. Testing the density and porosity of aluminiumis important for its development in various applications, including household appliances, aircraft industry, automotive, ships, and construction. The purpose of this research is to determine the density and porosity values of aluminium 7075 and aluminium 6061 samples. Experimental methods, such as the Archimedes method and the Fujitsu FSR A 300g x 0.001g analytical balance, are used to collect data and measure the mass density of the test specimens. The results show that aluminium 6061 has a higher density measurement value (3.302 g/cm3) compared to aluminium 7075 (2.144 g/cm3). The theoretical density calculation results also indicate that aluminium 7075 has a higher value (3.26 g/cm3) compared to aluminium 6061 (3.18 g/cm3). Additionally, aluminium 7075 has a higher porosity calculation value (34.2%) compared to aluminium 6061 (27.6%).